in vitro EVALUATION OF MEDICINAL PLANT EXTRACTS AS POTENTIAL ANTIMICROBIAL AGENTS FOR PATHOGENIC BACTERIA IN TILAPIA - García Pérez, Josué; Marroquín Mora, Dora (Kuxulkab', 2021)
Globally, aquaculture has grown dramatically in the last 50 years, causing negative impacts on fish health due to the increase in bacterial diseases. Tilapia producers usually treat diseases with a variety of antibiotics, promoting bacterial resistance. The objective of this study was to determine the antimicrobial effect of five extracts of medicinal plants against eight isolated pathogenic bacteria from tilapia cultures in Guatemala. Of the evaluated extracts, 'Syzygium aromaticum', 'Pimienta dioica' and 'Rosmarinus officinalis' inhibited the growth of six, five and three bacteria, respectively. The extracts presented broad spectrum antimicrobial characteristics, both for Gram negative and positive bacteria. The extracts with the highest antimicrobial activity were 'S. aromaticum' and 'R. officinalis', with minimal inhibitory and bactericidal concentrations between 300 ppm and 1,563 ppm. The extracts of 'Cinnamomum verum' and 'Lippia graveolens' did not inhibit the isolated pathogenic bacteria.
Keywords: Phytotherapy; Aquaculture; Microbiology; Guatemala